Serum amyloid A as a potential biomarker in inflammatory bowel diseases, especially in patients with low C-reactive protein - Stute, Marie; Kreysing, Martin; Zorn, Markus; Michl, Patrick; Gauss, Annika (International journal of molecular sciences, 2024)
The acute phase protein Serum Amyloid A (SAA) is synthesised by the liver in response to inflammatory stimuli. Previous studies have revealed that SAA may be a better biomarker of disease activity in inflammatory bowel disease (IBD) compared to C-reactive protein (CRP). This retrospective monocentric study evaluated whether SAA correlates with biomarkers like faecal calprotectin (FC), CRP, the Neutrophil to Lymphocyte ratio (NLR), the platelet count and clinical disease activity of IBD patients. Serum samples from the IBD outpatient clinic of the University Hospital Heidelberg were analysed for SAA concentrations if an FC concentration measurement was available from ±14 days to collection of the serum sample. Three hundred and six serum samples from 265 patients (166 with Crohn’s disease, 91 with ulcerative colitis and 8 with IBD unclassified) met the inclusion criteria. There was a significant positive correlation between SAA and FC, CRP, NLR, platelet count and the Simple Clinical Colitis Activity Index (SCCAI). The cut-off for SAA serum concentration at 4.55 mg/L achieved a sensitivity of 57.5% and a specificity of 69.7% for the detection of active inflammation in IBD. SAA may be used as an additional biomarker in the disease monitoring strategy of IBD patients, especially in patients with low CRP concentrations.
Gesehen am 08.08.2024